How effective are organ donation committees, and how can they be improved?. Issue 3 (2nd March 2019) - Silva, Geeth; Gor, Ratan; Patel, Nishil; Gupta, Shubham; Manivannan, Thulashie; Manu, Susan; Sharma, Ashwini; Gardiner, Dale; Cox, Benita
Abstract : Background: Organ donation committees were established in 2008 by NHS Blood and Transplant to improve the rates of organ donation in the UK. Aims: The aims of this study were three-fold: to review the role and structure of organ donation committees in England; to assess how effective organ donation committees are at driving improvements; and to make recommendations regarding the future role, responsibilities and structure of organ donation committees. Methods: This study adopted a cross-sectional mixed-methods research approach using questionnaires and semi-structured interviews. Results: There was a divergence between how each committee functioned and how effective they were in achieving their aims. Discussion: There were seven key findings which related to the effectiveness of organ donation committees. These included, but were not limited to, a lack of consistency in how the role of an organ donation committee was viewed by members of NHS Blood and Transplant; and that the influence a chair has within their respective NHS Trust is key to an organ donation committee being effective in achieving its aims. Conclusion: A framework and several recommendations were produced and aimed to help improve the effectiveness of organ donation committees.